The Seven husbands of Evelyn Hugo : a novel - Reid, Taylor Jenkins (London, United Kingdom : Simon & Schuster UK Ltd., 2017)
Aging and reclusive Hollywood movie icon Evelyn Hugo is finally ready to tell the truth about her glamorous and scandalous life. But when she chooses unknown magazine reporter Monique Grant for the job, no one is more astounded than Monique herself. Why her? Why now? Monique is not exactly on top of the world. Her husband has left her, and her professional life is going nowhere. Regardless of why Evelyn has selected her to write her biography, Monique is determined to use this opportunity to jumpstart her career. Summoned to Evelyn$1 (Bs luxurious apartment, Monique listens in fascination as the actress tells her story. From making her way to Los Angeles in the 1950s to her decision to leave show business in the '80s, and, of course, the seven husbands along the way, Evelyn unspools a tale of ruthless ambition, unexpected friendship, and a great forbidden love.s
Originally published: New York: Atria Books.
Keywords: ROMANCE -- FICTION